THE PARTICIPATION OF COOMUNITY IN MANGROVE FOREST MANAGEMENT IN RAWA MEKAR JAYA VILLAGE SUNGAI APIT SUBDISTRICT SIAK REGENCY - Morista Latersia Tarigan; Nurul Qomar; Defri Yoza (Jurnal Ilmu Ilmu Kehutanan, 2021)
Mangrove forest have a diversity of potential benefits for human life, so they need to be maintained so that their utilization can be sustainable. The surrounding community must be the main actor in the management of mangrove forests so that the benefits can be felt directly by the community. This study aims to determine the level and form of community participation in the management of Mangrove Forests in Rawa Mekar Jaya Village, Sungai Apit District, Siak Regency. Data were collected through observation, closed interviews with 73 respondents, in-depth interviews, and documentation studies. Data were analyzed descriptively qualitatively and processed with percentage techniques. The results showed that 69.87% of respondents had a low level of participation in all stages of mangrove forest management because management tended to be exclusively carried out by the Rumah Alam Bakau Tourism Conscious Group. 71.23% of respondents has a low level of participation at the decision making stage, implementation stage, and evaluation stage. 72.60% of respondents has a low participation rate at the stage of enjoying the results. Respondents who participated highly at every stage of management were those who joined the Rumah Alam Bakau Tourism Conscious Group. Forms of community participation in the management of mangrove forests are contributions of ideas / thoughts, energy, skills, and goods (property).